(untitled) (Al-Academy, 2021)
Action films employ many artistic and literary elements that contribute greatly to building the general meaning of the film and push the wheel of the film forward. The element of mystery and suspense is used as two basic elements in action films. The cinematic language in action films depends on global coding, which is not models as it might be. It is based on logic, rather as units that aspire to morphology and not their homogeneity as the physical sense, but as the logical harmony of interpretive authority and enlightenment and in action films as a field of communication and a field in its origin in which the signifier contrasts with the perceptions of the meaning and in it takes a certain number of units preventing each other and through what The researcher summarizes the problem of his research with the following question: How to use scientific encryption to build meaning in action films?Methodological framework: It includes the research problem, its importance, objectives, and terminology definition.The theoretical framework: It was divided into two topics that came as follows: The first topic: scientific coding, the second topic: the production of meaning: the third topic: the code and the production of meaning in the cinematic picture: After that, the researcher reached the indicators of the theoretical framework.Research procedures: The research method included the unit of analysis and sample analysis, which was the film (Saving Private Ryan) according to the indicators that the researcher came out with from the theoretical framework.After analyzing the sample, the researcher came to a number of findings and conclusions, including:1. The mark, in all its types, constitutes a point indicating many important information about the personality.2. The global coding provides an innovative formulation that works in the field of cinematic creativity.3. The global encryption occupies a great importance in action movies